(3LhGeY EUdGM GdefWbs - (3CHh GdMSjf RjO Hf QaGYI Hf eSYhO GdcGJHs; (3jYbhH Hf GSMGb, CHh jhSa, GHf GdScjJ,J (B224 (3g` s
(3ChdgG (B:s
(3jHOC HHGH aYd haYd HGNJdGa GdeYfi s
(3BNQgG (B:s
(3jfJgi HHGH BNQ s
(3GdfSNI HgG MhGTs
(3HChdg agQSs
(3cGf ai edc CHj HcQ Hf CHj GdaQGQS Hf eQga Hf GSeGeI Hf efbPs
(3Ydjg JedjcGJ CNQi s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
Keywords: (3GddZIs